Comparative Performance Study for Closed Loop Operation of an Adjustable Speed Permanent Magnet Synchronous Motor Drive with Different Controllers - Chiranjit Sain; Atanu Banerjee; Pabitra Kumar Biswas (Institute of Advanced Engineering and Science, 2016)
In this paper an extensive comparative study is carried out between PI and PID controlled closed loop model of an adjustable speed Permanent Magnet Synchronous Motor (PMSM) drive. The incorporation of Sinusoidal Pulse Width Modulation (SPWM) strategy establishes near sinusoidal armature phase currents and comparatively less torque ripples without sacrificing torque/weight ratio. In this closed loop model of PMSM drive, the information about reference speed is provided to a speed controller, to ensure that actual drive speed tracks the reference speed with ideally zero steady state speed error. The entire model of PMSM closed loop drive is divided into two loops, inner loop current and outer loop speed. By taking the different combinations of two classical controllers (PI & PID) related with two loop control structure, different approximations are carried out. Hence a typical comparative study is introduced to familiar with the different performance indices of the system corresponding to time domain and frequency domain specifications. Therefore overall performance of closed loop PMSM drive is tested and effectiveness of controllers will be determined for different combinations.